Comparison of some morphological parameters during the adolescence stage - Abdulla Elezi; Gentiana Beqa; Gresa Elezi (Kazimierz Wielki University, 2019)
The fastest changes in a child's growth and development occur during the puberty phase. The purpose of this research is based on this fact. The goal was to determine changes in the dynamics of growth and development of the morphological characteristics of children from age 12 to 15 years in the Municipality of Kamenica, Republic of Kosovo. To achieve this goal in this research are included 360 the masculine gender students of Elementary School "Dëshmorët e Kombit", in Kamenica. The students were divided into 4 group. Each group consisted of 90 children aged 12-15 years, total 360 children. The battery of 12 anthropometric variables (measures) was selected for the present research under the pressumption that there were four hypothetical latent anthropometric dimensions: the longitudinal dimensionality of skeleton, the transversal dimensionality of skeleton, circular dimensionality of skeleton, and the dimension of subcutaneous fat tissue. Basic statistical parameters were applied for all age groups: arithmetic mean and standard deviation. Within comparative statistics, they have been appliedAnalysis of variance (ANOVA) and Post Hoc multiple Comparisons, least significant difference (LSD). The results obtained shows that: 1. A more pronounced growth of children happens between years 12-13, 2. A more pronounced increase of the body mass occursbetween years 12-13 and body volume between 13-14years. 3. A more pronounced increase in the transversal dimensions of the body skeleton occurs at the age of 13-14 years. 4. Subcutaneous fat tissue it gradually decreases in all parts of the body by age 12- 15 years. During adolescence, growth does not develop evenly, arms and legs grows faster than body and we have a gradual decrease of subcutaneous fat tissue. We can emphasize that the phase of puberty should always be followed by meeting organic energy needs.